Expanding sexually transmitted infection screening among women and men engaging in transactional sex: the feasibility of field-based self-collection. (April 2013) - Roth, A M; Rosenberger, J G; Reece, M; Van Der Pol, B
Summary: Routine screening is a key component of sexually transmitted infection (STI) prevention and control; however, traditional programmes often fail to effectively reach men and women in hidden communities. To reduce prevalence, we must understand the programmatic features that would encourage utilization of services among asymptomatic individuals. Using incentivized snowball sampling, 44 women and men recently engaging in transactional sex were recruited (24 women, 20 men); median age 37 years. Respondents were offered the opportunity to collect genital, oropharyngeal and rectal samples for STI testing and completed a face-to-face interview about their experience with self-obtained sampling. Interviews were analysed using qualitative methods. Participants were unaware of potential risk for STI, but found self-sampling in non-clinical settings to be acceptable and preferable to clinic-based testing. All participants collected genital specimens; 96% and 4% collected oropharyngeal and rectal specimens, respectively. The burden of disease in this population was high: 38% tested positive for at least one STI. We detected multiple concomitant infections. Incorporating field collection of self-obtained samples into STI control programmes may increase utilization among high-risk populations unlikely to access clinic-based services. High infection rates indicate that individuals engaging in transactional sex would benefit from, and be responsive to, community-based self-sampling for STI screening.